Commonwealth Heads of Government Meeting 2007 (Henley Media Group Ltd. LondonGB, 2007)
Looks at ways of transforming societies, ensuring good governance, peace and prosperity and putting people at the heart of development. Focuses on natural resources and the environment. Highlights ways of connecting the Commonwealth and providing financing for development.
Keywords: ECONOMIC AND SOCIAL DEVELOPMENT